Strengthening conflict sensitivity in Kenya’s county climate change fund: Isiolo county - Medina, Leonardo; Schapendonk, Frans; Jaskolski, Martina; Osumba, Joab; Jebiwott, Alice; Mutuku, Munini; Takaindisa, Joyce; Giti, Daniel (2025)
This policy brief examines the integration of conflict sensitivity within Kenya’s County Climate Change Fund (CCCF) mechanism, focusing on Isiolo County. Isiolo, a climate-vulnerable and ethnically diverse pastoralist region, experiences recurrent droughts, erratic rainfall, and competition over scarce resources, making conflict-sensitive adaptation crucial. The study highlights how the CCCF strengthens multi-level governance, incorporates customary systems such as the Borana Dedha, embeds conflict risks into vulnerability assessments, and promotes inclusive representation of women, youth, and marginalized groups. These features demonstrate the CCCF’s strong potential to align climate adaptation with peacebuilding outcomes. However, the analysis also identifies key challenges, including weak cross-boundary planning, informal engagement of peace actors, lack of transparency in funding, interruptions in budget allocations, and limited monitoring of peace outcomes. The brief concludes that embedding conflict-sensitive approaches (through institutionalizing peace roles, enhancing accountability, ensuring funding continuity, and systematically tracking socio-political impacts) can safeguard adaptation investments and strengthen community resilience.